Adaptasi dan validasi Skala Stres Peran (Role Stressor Scale) dalam budaya Indonesia: Eksplorasi ekuivalensi konstruk dan analisis faktor konfirmatori - Silvia Kristanti Tri Febriana; Fajrianthi Fajrianthi; Fendy Suhariadi (Jurnal Psikologi Sosial, 2022)
This study aims to conduct instrument adaptation of role stressor scale developed by Peterson et al. (1995) in the Indonesian language and culture. The research was performed in two studies. In study 1, the translation process and a construct equivalence test was carried out involving 6 translators, 3 expert reviewers, and 10 laypeople for cognitive debriefing. Study 2 involved 232 subjects of workers in Indonesia and examined the validity using confirmatory factor analysis. The entire adaptation process refers to the procedures of the 2016 International Test Commission (ITC) Guidelines for Test Adaptation. The CFA results showed that the measurement models of the role stressor instrument fitted the 3 factors model. Overall, this study showed that the Indonesian version of the role stressor instrument is valid and reliable, therefore, it can be utilized to measure the role stressors in Indonesia